Detecting unusual changes of users consumption - Britos, Paola Verónica (2008)
The points being approached in this paper are: the problem of detecting unusual changes of consumption in mobile phone users, the corresponding building of data structures which represent the recent and historic users' behavior bearing in mind the information included in a call, and the complexity of the construction of a function with so many variables where the parameterization is not always known.